Caucasus hospitality as a component of the tourist brand of the North Caucasus federal district: formation factors and promotion trends - O. I. Belozerova (Вестник Северо-Кавказского федерального университета, 2023)
The purpose of the study is to clarify the essence of the concept of «Caucasus hospitality», to determine the factors of its formation and role in promoting the tourist brand of the North Caucasus Federal District. The introduction to the article discusses the current state of tourism in the North Caucasus Federal District, presents the dynamics of tourist flows in the studied destination over the past few years, and analyzes individual indicators of the development of the hospitality sector in the region. The main part of the work describes the tools for marketing promotion of the North Caucasus as a tourist destination. With the help of the content analysis of the theoretical provisions presented in scientific sources, the essence of Caucasus hospitality is specified and its key characteristics are highlighted. The main results and novelty of the study was to determine, using a systematic approach, the basic prerequisites and priority areas for implementing the concept of Caucasus hospitality in the North Caucasus as a tool to strengthen the tourism brand of the region and achieve uniform service standards for tourism enterprises in the North Caucasus Federal District. It is concluded that a strong brand of a tourist destination forms a special loyal attitude of tourists towards it, increases the attractiveness and prestige of visiting this territory.